Gerenciamento das fontes no cariri: uma perspectiva integrada e multidisciplinar - Sabiá, Rodolfo José (2000)
Since the past century, the springs of the Cariri are of great importance for the development of agricultural, social, and cultural activities. The “Water Partition Act” of the Municipality of Crato, promulgated in 1854, was the first legal instrument for the administration of there waters, later adopted by other municipalities of the region. However, modern legislation is in contradiction with the Act, as Law 9433/97 determines that water is of public dominion. At present, little use is made of spring waters, mainly due to a lack of administration of the resource. An inventory of the springs and measures to preserve quality and quality. We monitored monthly the discharge of the springs Bom Jesus and João Coelho in Caldas, and Farias in the district of Arajara/ Barbalha and pluviosity on the top of the Araripe Plateau through instruments installed by us. In addition, we made a survey of the actual use of the waters from these springs. For the Farias springs, a delay of 5 months of maximum discharge in relation to rainfall was observed, confirming prior results of seasonal variations. However, for those in Caldas, a delay was of one month only. In the light of these variations a monitoring propane is needed in order to avoid allotment of an inexisting resource.